Benda Asing Faring Esofagus di Bagian/KSM THT-KL RSUP Prof. Dr. R. D. Kandou Manado Periode Januari 2014 – Desember 2016 - Wallah, Illan P.; Mengko, Steward K.; Tumbel, R. E.C. (e-CliniC, 2017)
Abstract: Ingested foreign bodies are one of the most common emergencies in Ear, Nose and Throat (ENT)-Head and Neck Surgery that can be found in all ages throughout the world. Ingested foreign bodies can usually be lodged in oropharynx, hypopharynx, or esophagus. This study was aimed to describe the profile of pharyngeal and esophageal foreign body patients in the Department of ENT-Head and Neck Surgery Prof. Dr. R. D. Kandou Hospital Manado in the period of January 2014-December 2016. This was a descriptive retrospective study. Samples were patients recorded in the register book and the medical record database which from their history, physical examination and diagnostic investigation were firstly diagnosed as pharyngeal or esophageal foreign body. Variables in this study were gender, age, type of foreign body, location of foreign body, and treatment success rate. The results showed that there were 25% of pharyngeal foreign bodiy cases and 75% of esophageal foreign body cases. Most cases were males (57.3%), age ≥51 years (25.3%) and 0-10 years (24.0%). The most common types of foreign bodies found were bones and dentures, each of 25 cases. The most common location written was in general. Conclusion: In foreign body cases of ENT-Head and Neck Surgery, esophageal foreign body cases were more common compared to pharyngeal foreign body cases.Keywords: foreign bodies, pharynx, esophagus Abstrak: Benda asing yang tertelan merupakan salah satu kegawatdaruratan bidang THT-KL yang tersering dan dapat ditemukan pada semua usia di seluruh dunia. Benda asing yang tertelan biasanya dapat tersangkut pada orofaring, hipofaring atau esofagus. Penelitian ini bertujuan untuk menguraikan profil penderita benda asing faring esofagus di Bagian/KSM THT-KL RSUP Prof. Dr. R. D. Kandou Manado pada periode Januari 2014 – Desember 2016. Jenis penelitian ialah retrospektif deskriptif. Sampel ialah pasien yang tercatat pada buku register dan database rekam medis yang dari anamnesis, pemeriksaan fisik dan penunjang terdiagnosis sebagai benda asing faring esofagus pertama kali di Bagian/KSM THT-KL RSUP Prof. Dr. R. D. Kandou Manado pada periode pengamatan. Variabel penelitian ini ialah jenis kelamin, umur, jenis benda asing, lokasi benda asing, dan tingkat keberhasilan penanganan. Terdapat 25% kasus benda asing faring dan 75% kasus benda asing esofagus. Kasus benda asing lebih sering terjadi pada jenis kelamin laki-laki (57,3%), usia ≥51 tahun (25,3%) dan 0-10 tahun (24,0%). Jenis benda asing yang tersering ditemukan ialah tulang dan gigi palsu, masing-masing 25 kasus. Penulisan lokasi paling sering ialah secara umum. Simpulan: Pada kasus benda asing THT-KL dalam periode pengamatan tiga tahun ini, kasus benda asing esofagus lebih sering ditemukan dibanding kasus benda asing faring.Kata kunci: benda asing, faring, esofagus